Komunikacja marketingowa jako instrument w kształtowaniu wizerunku polityka - Cieślicki, Marcin (My University, 2011)
Niniejsza praca poświęcona jest tematyce dotyczącej komunikacji marketingowej, a szczególnie roli niewerbalnej w kreowaniu wizerunku kandydata. W celu uzyskania potrzebnych informacji, 100 respondentów zostało poddanych badaniu w formie ankiety kwestionariusza z pytaniami zamkniętymi. Z analizy pytań wynika, że mowa ciała owszem jest istotna, ale nie jest najważniejszym czynnikiem przy wyborze kandydata idealnego.

This dissertation is concentrated on studying marketing communication which influence on politician's image creation. For this study questionnaire is one of the ways of collecting data for the purpose of study. The questionnaire is based on questions closed. The questionnaire was distributed among 100 respondents. 100 of questionnaires were collected and analyzed. According to the research and analysis of the findings the "body language" plays significant role, but it is not the most important aspect which influence on the choice of politician.
Marketing communication as a main factor in the creation of politycian’s image
Keywords: marketing polityczny; wizerunek polityczny; komunikowanie polityczne